ChemInform Abstract: Ruthenium Catalyzed Intramolecular C—S Coupling Reactions: Synthetic Scope and Mechanistic Insight. Issue 25 (June 2016) - Sharma, Shivani; Pathare, Ramdas S.; Maurya, Antim K.; Gopal, Kandasamy; Roy, Tapta Kanchan; Sawant, Devesh M.; Pardasani, Ram T.
Abstract: Kinetic, isotope labeling, and computational studies reveal the involvement of an electrophilic ruthenation pathway instead of a direct C—H activation for this reaction.